Methodology of character education - Jo’rayeva Nasibakhan G’aniyevna (Peerian Journals Publishing, 2023)
this article provides information on the methodology of teaching Khusnihat, the basic principles of Khusnihat teaching methodology, the benefits of Khusnihat teaching methodology, the implementation of Khusnihat teaching methodology in the textbook
Keywords: Khusnihat educational methodology; modern pedagogy; principle